Item Analysis of a Physics Technological Literacy Test on Work and Energy - Abdul Rafid Fakhrun Gani; Dewi Wulandari; Yuni Warty (Al-Musannif, 2026)
This study aimed to develop and analyze a physics technological literacy test instrument on the topic of work and energy for senior high school students. This study addresses the limited availability of technological literacy assessment instruments specifically designed for the topic of work and energy in physics education. The research used a Research and Development (R&D) approach with the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The instrument was developed based on three dimensions of technological literacy: knowledge, capabilities, and critical thinking and decision making. The study involved 200 students from several senior high schools in Binjai City, Indonesia. Data were analyzed using validity, reliability, and Rasch model analyses to evaluate the quality of the instrument. The results showed that the instrument was highly feasible, with evaluation expert validation of 92,13% and material expert validation of 90,4%. Practicality testing also indicated that the instrument was practical and easy to use. All items were categorized as valid and reliable, with a Cronbach’s Alpha coefficient of 0.935. The Rasch analysis demonstrated that the instrument could accurately measure students’ technological literacy abilities across various ability levels. The findings indicate that the developed instrument is valid, reliable, practical, and effective for measuring students’ technological literacy in physics learning, and it can serve as an assessment tool for teachers to evaluate and improve students’ technological literacy skills.